2016
DOI: 10.1016/j.physletb.2016.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Localization and mass spectrum of q -form fields on branes

Abstract: In this paper, we investigate localization of a bulk massless q-form field on codimension-one branes by using a new Kaluza-Klein (KK) decomposition, for which there are two types of KK modes for the bulk q-form field, the q-form and (q − 1)-form modes. The first modes may be massive or massless while the second ones are all massless. These two types of KK modes satisfy two Schrödinger-like equations. For a five-dimensional brane model with a finite extra dimension, the spectrum of a bulk 3-form field on the br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
(86 reference statements)
0
15
0
Order By: Relevance
“…In Refs. [31][32][33][34] with the general KK decomposition (1) the gauge invariance of massive vector KK modes for a free bulk U(1) gauge field in branes with codimension one or more was discussed. Here we give a brief review on a brane with codimension one.…”
Section: Gauge Invariant Kk Modes Of a Free Bulk U(1) Gauge Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…In Refs. [31][32][33][34] with the general KK decomposition (1) the gauge invariance of massive vector KK modes for a free bulk U(1) gauge field in branes with codimension one or more was discussed. Here we give a brief review on a brane with codimension one.…”
Section: Gauge Invariant Kk Modes Of a Free Bulk U(1) Gauge Fieldmentioning
confidence: 99%
“…Thus it is natural to ask whether the Lagrangian of these massive vector KK modes is gauge a e-mail: fuche13@mail.xjtu.edu.cn (corresponding author) b e-mail: zhaozhh78@sdust.edu.cn c e-mail: electron1@stu.xjtu.edu.cn invariant. It was found that for a free bulk U(1) gauge field, with a gauge free KK decomposition, some scalar KK modes coupling with the vector ones appear [31][32][33][34]. Because of these scalar KK modes the massive vector ones were identified to be gauge invariant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equations (20) and (25), with the potentials (21) and (26), governs the extra dimension component of KR and vector fields respectively. Now we must analyze the localization of the zero mode of the KR and vector fields.…”
Section: Kalb-ramond Coupled With a Rank Two Geometric Tensormentioning
confidence: 99%
“…Among them, the U (1) vector field (1-form) and the Kalb-Ramond field (2-form) has an important status. The study of the confinement of these two fields and another p-form was already widely performed in the literature [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. There are other related issues, such as that p-form fields have been used to provide the stabilization of the radius in RS-I model [50]; or, that one introduced torsion in RS-I scenarios [51]; or still, one addressed generation of inflation or gravitational waves [52,53]; among other issues [54][55][56].…”
Section: Introductionmentioning
confidence: 99%